Gaya Kepemimpinan Kepala BNN Dalam Memotivasi Karyawan Pada Kegiatan Rehabilitasi Penyalahgunaan Narkoba di Klinik Pratama: (The Leadership Style of the Head of the National Narcotics Agency of the Republic of Indonesia in Motivating Employees on Drug Abuse Rehabilitation Activities in Primary Clinics) - Suradarwansyah, Suradarwansyah; Muazza, Muazza (Indonesian Educational Administration and Leadership Journal (IDEAL), 2020)
This study aims to determine how the leadership style applied by the head of the National Narcotics Agency in motivating employees on the rehabilitation activities of narcotics abusers in the Primary clinic and to determine the impact of the leadership style that has been applied by the head of the National Narcotics Agency on employees’ performance. This research uses a qualitative method with a case study design, where researchers go directly to the field and socialize with employees and leaders, so the researchers know more deeply about the leadership style of the head of the National Narcotics Agency of the Regency (BNNK) of Batanghari in motivating employees. The leadership style in BNNK Batanghari in improving the employee’s performance is categorized in democratic, charismatic and autocratic. Democratic leadership style and charismatic leadership style are the dominant leadership styles that are applied by the head of BNNK Batanghari. While the autocratic style is only adapted to the situation, the democratic leadership style can be seen by the head of the BNNK opens space for subordinates to submit criticisms and suggestions in making decisions and supports subordinates to develop their potential. Charismatic leadership style is known that the head of the National Narcotics Agency has become a good role model for subordinates to become an admired person. The autocratic leadership style encourages subordinates to discipline in working and completing the work on time. These findings suggest that a leader should maintain what has been achieved, so that the performance of leaders and employees can drive BNNK institutions to be a greater institution. Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana gaya kepemimpinan yang diterapkan oleh kepala BNN dalam memotivasi karyawan pada kegiatan rehabilitasi penyalahguna narkotika di klinik Pratama serta untuk mengetahui dampak yang ditimbulkan dari gaya kepemimpinan yang telah diterapkan kepala BNN terhadap kinerja karyawan. Penelitian ini menggunakan metode kualitatif dengan rancangan studi kasus. Dimana peneliti terjun langsung ke lapangan dan bersosialisasi dengan karyawan dan pimpinan, agar peneliti mengetahui secara lebih mendalam tentang gaya kepemimpinan kepala BNNK Batanghari dalam memotivasi karyawan. Gaya kepemimpinan kepala BNNK Batanghari dalam meningkatkan kinerja pegawai adalah gaya kepemimpinan, demokratis, kharismatis dan otokratis. Gaya kepemimpinan demokratis dan gaya kepemimpinan kharismatik merupakan gaya kepemimpinan yang dominan yang diterapkan oleh kepala BNN. Sedangkan gaya otokratis hanya disesuaikan dengan situasi yang ada. Gaya kepemimpinan demokratis dapat dilihat bahwa kepala BNN membuka ruang bagi bawahan untuk menyampaikan kritik dan saran dalam membuat keputusan serta mendukung bawahan untuk mengembangkan potensi. Gaya kepemimpinan kharismatik diketahui bahwa kepala BNN menjadi teladan yang baik bagi bawahan sehingga menjadi orang yang dikagumi. Sedangkan gaya kepemimpinan otokratis mendorong bawahan untuk disiplin dalam bekerja dan menyelesaikan pekerjaan tepat waktu. Dari temuan tersebut menyarankan agar seorang pemimpin hendaklah mempertahankan apa yang sudah dicapai saat ini sehingga prestasi kerja pimpinan dan karyawan dapat membawa institusi BNN lebih maju.